THU0354 Impact of biologic therapy in sjogren's syndromepatients with overlapping autoimmune diseases or extraglandular manifestations. a systematic review of literature. (12th June 2018) - Fragoulis, G.E.; Nikiphorou, E.; Alunno, A.; Ng, F.; Tzioufas, A.G.
Abstract : Background: Treatment of Sjogren's syndrome (SS) has traditionally focused on conventional synthetic DMARDs (csDMARDs), with encouraging evidence on the benefit of biologic therapies emerging, mainly for treatment of SS extraglandular manifestations. Overlapping autoimmune diseases in SS are poorly studied; yet evidence primarily from case reports suggest a beneficial effect with biologics. Objectives: To systematically review the literature on the treatment of SS with biologics, taking a focus on case reports and overlapping autoimmune conditions or extraglandular manifestations (defined here as those described in the EULAR SS disease activity index - ESSDAI). Methods: A literature review was performed independently by two reviewers, using Pubmed and the following search terms: "Sjogren" or "Sjogren's" AND any of the following: "biologics", "Etanercept", "Adalimumab", "Infliximab", "Golimumab", "Certolizumab", "Tocilizumab", "Abatacept", "Rituximab", "Belimumab", "Secukinumab", "Ustekinumab" and "Anakinra". Inclusion criteria were: articles in English; published until January 2018; case reports of patients with primary or secondary SS. Initial screening was based on title/abstract, followed by full-text review for articles fulfilling inclusion criteria. For articles written in a different language, information was obtained from abstract if available, otherwise excluded. Concordance in article screening was 95% across the two reviewers. Data extraction focused on reporting overlapping autoimmune diseases and extraglandular manifestations, treatment and response data. Results: Out of 679 papers screened, 39 articles were included. 22 overlapping autoimmune conditions were reported in 22 SS patients (table 1). Most of the patients were treated with Rituximab (63.6%), while TNF-inhibitors (22.7%), Tocilizumab (9.1%) and Ustekinumab (4.5%) were also used. Concurrent treatment with csDMARDs and steroids was used in 28.6% and 42.9% of the cases, respectively. 61.9% and 13.6% of the patients were csDMARDs- and biologic- experienced, respectively. Good response of overlapping condition was seen in 86.4% of them, while in 13.6%, control or partial response was reported. Although, most of the studies do not mention the effect of biologic treatment on SS, general 'improvement' was mentioned in 4 cases, while arthritis was improved in 6 patients, 4 of which had secondary SS. In terms of extraglandular manifestations (e.g cryoglobulinemic vasculitis, interstitial nephritis) 18 were reported. 16 (88.8%) patients received Rituximab (one of them in combination with Belimumab), while 2 (11.1%) were treated with TNF-inhibitors. 11.1% and 61.1% of them received concurrent treatment with csDMARDS and steroids, respectively. 55.5% and 11.1% of the patients were csDMARDs- and biologics- experienced, respectively. Extraglandular manifestations responded well in the majority (83.3%) of the patients, with the remaining having partial or late response. SS and arthritis 'improvement' was mentioned in 5 and 1 patients, respectively. Table 1 Biologic treatments used for overlapping autoimmune conditions in SS patients. csDMARDs: conventional synthetic Disease Modifying Antirheumatic Drugs, NA: Not Applicable, Joints: improvement of arthritis. ^SS response was defined as clinical improvement of sicca symptomatology or improvement in ESSDAI. Improvement of arthritis was reported separately. † cases of secondary Sjogren's syndrome (3 cases co-existing with RA and one case with SLE) Conclusions: Treatment with biologic DMARDs, sometimes accompanied by steroids, appears to be beneficial also in treating overlapping autoimmune diseases as well as some extraglandular manifestations in SS patients. Disclosure of Interest: None declared